2010
DOI: 10.1371/journal.pone.0009154
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Processing and Alternatively Spliced Transcripts of Factor VIII: Potential Implications for Coagulation Cascades and Pulmonary Hypertension

Abstract: BackgroundCoagulation factor VIII (FVIII) deficiency leads to haemophilia A. Conversely, elevated plasma levels are a strong predictor of recurrent venous thromboemboli and pulmonary hypertension phenotypes in which in situ thromboses are implicated. Extrahepatic sources of plasma FVIII are implicated, but have remained elusive.Methodology/Principal FindingsImmunohistochemistry of normal human lung tissue, and confocal microscopy, flow cytometry, and ELISA quantification of conditioned media from normal primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…2,[7][8][9][10][11] Although it remains to be clarified whether endothelial cells from various vascular beds share this property, it is thought that nonhepatic endothelial cells might be a major source of FVIII secretion and contribute to the DDAVP-releasable pool in vivo. We wanted to know whether targeting FVIII expression to endothelial cells can reestablish a regulated releasable pool of FVIII and correct the hemophilia A phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[7][8][9][10][11] Although it remains to be clarified whether endothelial cells from various vascular beds share this property, it is thought that nonhepatic endothelial cells might be a major source of FVIII secretion and contribute to the DDAVP-releasable pool in vivo. We wanted to know whether targeting FVIII expression to endothelial cells can reestablish a regulated releasable pool of FVIII and correct the hemophilia A phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] It has been proposed that synthesis of FVIII occurs in a subpopulation of endothelial cells. [6][7][8][9][10][11] Targeting FVIII expression to lung endothelial cells 12 or liver sinusoidal endothelial cells 13 has been shown to result in phenotypic correction in hemophilia A mice. In vitro studies performed in our laboratory have demonstrated that FVIII traffics to storage granules in a von Willebrand factor (VWF)-dependent manner and is coreleased with VWF by agonist stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…The most plausible explanation for this effect may lie in the way in which VWF and FVIII are naturally synthesized and released by endothelial cells. Both FVIII and ultra-large multimers of VWF (ULVWF) are packaged in the WeibelPalade bodies of select types of primary endothelial cells [5,6]. Upon secretion of the granules, strings of ULVWF anchored on the cell surface are cleaved by the metalloprotease ADAMTS13 into smaller FVIII/ VWF multimers [6,7], while pH-induced dissociation of VWF propeptide allows both FVIII to bind and FVIII/VWF multimers to adopt a globular conformation [8].…”
Section: Referencesmentioning
confidence: 99%
“…18 Several groups reported recently that subsets of endothelial cells exist that synthesize FVIII and store it with VWF in WPBs. [19][20][21][22] Previously, it was demonstrated that overexpression of FVIII in endothelial cells results in FVIII targeting to WPBs. [23][24][25][26] The targeting signal for FVIII sorting to WPBs is currently unclear, although the typical high-affinity interaction with VWF seems not required.…”
mentioning
confidence: 99%